Aaron Copland in Latin America : music and cultural politics - Hess, Carol A. (Urbana : University of Illinois Press, 2023)
"Between 1941 and 1963, Aaron Copland made four government-sponsored tours of Latin America that drew extensive attention at home and abroad. Interviews with eyewitnesses, previously untapped Latin American press accounts, and Copland's diaries inform Carol A. Hess's in-depth examination of the composer's approach to cultural diplomacy. As Hess shows, Copland's tours facilitated an exchange of music and ideas with Latin American composers while capturing the tenor of United States diplomatic efforts at various points in history. In Latin America, Copland's introduced works by U.S. composers, including himself, through lectures, radio broadcasts, live performance, and conversations. Back at home, he used his celebrity to draw attention to regional composers he admired. Hess's focus on Latin America's reception of Copland provides a variety of outside perspectives on the composer and his mission. She also teases out the broader meanings behind reviews of Copland and examines his critics in the context of their backgrounds, training, aesthetics, and politics"--
Part I : A citizen diplomat prepares. Introduction ; Copland and the beginnings of U.S. cultural diplomacy ; Copland as good neighbor : A musical diplomat and the OIAA -- Part II : Copland, Latin America, and World War II. Diplomat "in the field" ; Copland in Argentina ; Copland in Brazil ; Copland in Chile ; "The fiery trial through which we pass" : The Americas at war -- Part III : Copland, Latin America, and the Postwar. Copland, Latin America, and the early Cold War ; Shifting ground : Copland, Latin America, and the crisis of modernism ; A "living refutation to Communist-inspired lies" : Copland in Latin America in the sixties ; Latin American classical music and memory.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 11, 2023).
eBooks on EBSCOhost
Keywords: Copland, Aaron, -- 1900-1990 -- Travel -- Latin America; Copland, Aaron, -- 1900-1990; Music and diplomacy -- Latin America -- History -- 20th century; Cultural diplomacy -- Latin America -- History -- 20th century; Pan-Americanism -- History -- 20th century; Musique et diplomatie -- Amérique latine -- Histoire -- 20e siècle.; Diplomatie culturelle -- Amérique latine -- Histoire -- 20e siècle.; Panaméricanisme -- Histoire -- 20e siècle.; MUSIC / Genres & Styles / Classical; BIOGRAPHY & AUTOBIOGRAPHY / Music; Cultural diplomacy; Music and diplomacy; Pan-Americanism; Travel; Latin America; Music; Music; 1900-1999; History